IMPLEMENTATION OF HALAL VALUE CHAIN IN BLOCKCHAIN-BASED HALAL INDUSTRY IN ACEH PROVINCE - Fuadi, Fuadi; Razali, Ramadhan; Juanda, Reza; Arliasnyah, Arliasnyah; Nurul Aulia; Muhammad Ikram; Putri Ramadhani (International Journal of Economic, Business, Accounting, Agriculture Management and Sharia Administration (IJEBAS), 2022)
The purpose of this research is to find out the importance of implementing databases in block chain-based supply chains. As for the object of the research, all SMEs in Aceh have the characteristics of exporting their products abroad. as for this type of research is qualitative research with data collection methods, namely interviews. The conclusion obtained is that in the supply chain in Aceh province, SMEs need a serious data revolution. This is based on the growing demand for halal products in the province of Aceh. Therefore, SMEs in Aceh Province need blockchain as a database in the supply chain. To maximize this, cooperation from the government, the community, and business actors is needed